Challenges home and international students face in group work at a Dutch university. (4th July 2022) - Popov, Vitaliy; Brinkman, Dine; Fortuin, Karen P. J.; Lie, Rico; Li, Yaoran
ABSTRACT : This study aims to provide insights into the challenges that home and international students experience when collaborating in mixed groups. A selection of 261 reflective journals written by students as part of the Intercultural Communication Skills course at a Dutch university in the domains of life sciences and engineering was analyzed. These journals were written by 210 Dutch ( =  home) students, 22 European (non-Dutch) students, and 29 Asian students. The quantitative analysis showed that the main challenges were group management, contribution to group work, and feedback. Asian students reported challenges related to feedback significantly more often compared to Dutch and other European students. The qualitative analysis showed that Dutch, other European, and Asian students' concerns differed in terms of interaction and communication styles stemming from their various cultures of learning.